Unlocking success: key elements of sustainable business models in the wooden multistory building sector - Nagy, Emil; Jussila, Jaakko; Häyrinen, Liina; Lähtinen, Katja; Mark-Herbert, Cecilia; Toivonen, Ritva; Toppinen, Anne; Roos, Anders (Frontiers in Sustainability, 2024)
Few studies have investigated the processes and strategic interactions among the Wooden Multistory Construction (WMC) industry actors, its customers, and local policymakers. Further insights into this field are needed for a sustainability transition in the construction sector. This study aims to explain WMC’s corporate sustainability strategies for co-creation with customers and municipalities. This was based on interviews with key informants in the sector and WMC actors using three case studies in Sweden. Our interviews focused on business processes, interactions with users and municipalities, sustainability, and innovation in the WMC market. The findings reflect the notion of a slow transition in the Swedish WMC market toward using more wood as a bearing structure, which is supported by the competitive advantages and climate performance of wood. The three case studies indicated that the corporate focus is currently placed on incremental improvements in operations, price competitiveness, and successful project management. However, in contexts where wood construction is seen as a unique advantage, collaborations between the construction industry and end users have developed and served as novel platforms for WMC market development. The study concludes that WMCl growth hinges on the industry’s housing offerings prioritizing quality, affordability, and swift construction.